China Economic Update, June 2014 - Smits, Karlis (World Bank, Beijing, 2015)
Chinas economic growth is gradually slowing as the structural transformation of the economy continues. Output grew by 7.7 percent in 2013, matching its 2012 growth rate and exceeding the governments 7.5 percent indicative target. In recent months economic activity, including industrial production, started to show signs of acceleration. The recent acceleration, expected to continue into the next two quarters, is partly reflecting the effect of new growth-supporting measures, robust consumption, and a recovery of external demand. Chinas growth will continue to moderate over the medium term, and the structural shifts will become more evident. Growth in China is expected to decrease marginally to 7.6 percent in 2014 and 7.5 percent in 2015, from 7.7 percent in 2013. Fiscal and financial sector reforms are needed to address financial stability risks in the medium run. The first task involves effectively managing the process of rapid credit growth, including less well-regulated shadow banking system. The second involves gradual and orderly deleveraging of large stock of local government debt accumulated through off-budget and quasi-fiscal platforms.